Update on biologic safety for patients with psoriasis during pregnancy - Martina L. Porter; Stephen J. Lockwood; Alexa B. Kimball (Wolters Kluwer, 2017)
Biologic agents have become more common to treat patients with psoriasis, but concerns about their effect on pregnancy and lactation often preclude this treatment during these time periods. During the past decade, we have gained a much better understanding of the course of psoriasis during pregnancy and the safety of the use of biologic agents during pregnancy and lactation. Under certain circumstances, biologic agents can be considered appropriate treatment options for patients who are pregnant or lactating. Keywords: psoriasis, pregnancy, lactation, biologic agents, TNF-alpha inhibitors